Health determinants and cardiovascular risk factors in medicine students: A narrative review of the literature (Research, Society and Development, 2021)
Objective: To evaluate, through a literature review, health determinants and factors related to cardiovascular changes in medical students. Methodology: a search was made in the databases of Medline (PubMed) and Scielo, using the descriptors: “cardiovascular diseases”, “medical students” and “risk factors” in Portuguese and “cardiovascular diseases”, “medical students” and “risk factors”, in English. The inclusion criteria were: to be articles in English, Portuguese or Spanish; be a study with adults; be related to the object of study; as well as having full text and published between the years 2014 to 2021. This process resulted in 11 articles eligible for full reading and analysis. Results and discussions: Coelho et al. (2005) and Schimidt et al. (2011) cited a greater sedentary lifestyle linked to less time available, and a high level of stress-related to study load among medical students. As for overweight, data by Jardim et al. (2014) revealed that university education in the health field did not interfere with the increase in the prevalence of excessive weight gain over the years. Conclusion: Among the factors that could explain the medical students' exposure to cardiovascular risk factors are arterial hypertension, poor diet, sedentary lifestyle, dyslipidemia, stress, and metabolic changes. About the higher prevalence or cardiovascular risk factors in male students, it is possible that this results from a greater exposure to alcoholism and smoking.